Common peroneal nerve rupture with multiple ligament knee injury: A case report - Kaoru Tada; Masashi Matsuta; Mika Akahane; Atsuro Murai; Hiroyuki Tsuchiya (Clinical Case Reports, 2022)
Abstract In peroneal nerve palsy with closed knee injury, most of the case improves by follow‐up. We present a case of peroneal nerve rupture with closed multiple ligament knee injury, requiring nerve transplantation. In multiple ligament knee injury, it is necessary to consider the possibility of peroneal nerve rupture.